A wearable system to measure speed and phase durations during each cycle of classical cross-country skiing - Fasel, B.; Favre, J.; Chardonnens, J.; Aminian, K. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
This study introduced a valid and sensitive system to measure the temporal signature and cycle speed of cross-skiing movement. The system has a high potential for professional and recreational applications as it can be used in any fields without assistance.